Periprosthetic Leakage in Tracheoesophageal Prosthesis: Proposal of a Standardized Therapeutic Algorithm. (September 2021) - Parrilla, Claudio; Longobardi, Ylenia; Galli, Jacopo; Rigante, Mario; Paludetti, Gaetano; Bussu, Francesco; Scarano, Emanuele
Objective: Periprosthetic leakage represents the most demanding long-term complication in the voice prosthesis rehabilitation. The aim of this article is to discuss the various causes of periprosthetic leakage and to propose a systematic management algorithm. Study Design: Retrospective cohort study. Setting: Otolaryngology clinic of the University Polyclinic A. Gemelli–IRCCS Foundation. Methods: The study included 115 patients with voice prosthesis who were treated from December 2014 to December 2019. All patients who experienced periprosthetic leakage were treated with the same step-by-step therapeutic approach until it was successful. Incidence, management, and success rate of every attempt are analyzed and discussed. Results: Periprosthetic leakage was reported 330 times by 82 patients in 1374 clinic accesses. Radiotherapy, timing of tracheoesophageal puncture, and type of total laryngectomy (primary or salvage) did not influence the incidence of periprosthetic leakage. Salvage total laryngectomy increases the risk of more clinically relevant leakages. Conclusion: By using a systematic algorithm with a step-by-step standardized approach, periprosthetic leakage management could become a less treacherous issue.